IMPLEMENTATION OF THE DIDACTIC MODEL OF DEVELOPMENT OF HEALTH-SAVING COMPETENCE OF TEACHERS OF THE SUBJECT «INTEGRATED COURSE: HEALTH, SAFETY AND WELL-BEING» - Ємець, А.; Жамардій, В.; Кононец, Н.; Літвінов, П.; Скріннік, Є. (Нові горизонти педагогічної майстерності: від традицій до інновацій, 2025)
The aim of the study is to develop a didactic model for the development of health-saving competence of teachers of the subject «Integrated course: health, safety and well-being» and to present the results of its implementation. Experimental verification of the didactic model of development of health-saving competence of teachers of the subject «Integrated course: health, safety and well-being» was carried out with the help of a local pedagogical experiment in March 2024. 55 teachers of the subject «Integrated course: health, safety and well-being» from schools of Poltava and Poltava region were selected to participate in the experiment, who agreed to participate in the approbation of the didactic model on the basis of Poltava Academy of Continuing Education named after M. V. Ostrogradsky. Experimental verification of the developed methodology showed that in general the level of development of health-saving competence of teachers of the subject «Integrated course: health, safety and well-being» increased after the introduction of the proposed didactic conditions.